Does portfolio emulation outperform its target funds?. (August 2013) - Chen, Zhe; Foster, F Douglas; Gallagher, David R; Lee, Adrian D
An emulation fund is designed to reduce trading activity, thereby lowering costs, for a multi-manager fund. It does this by delaying, and potentially combining, trading decisions from each employed fund manager to eliminate offsetting trades (e.g. one manager may buy a stock for her fund while another manager sells the same stock at approximately the same time for his fund). While lowering transaction costs is a key benefit of an emulation strategy, there has been little research that compares the reduction in transaction costs with the opportunity costs of delaying trade. Using reported equity trades for a large Australian pension fund, we simulate the consequences of an emulation strategy. We find that simulated emulation trades underperform those trades made by the employed (or target) fund over our sample period. That is, the opportunity cost of delayed trading significantly outweighs transaction cost reductions. Overall, we do not find strong evidence to support emulation from a cost–benefit perspective before management fees and taxes.